Upaya Guru dalam Meningkatkan Keaktifan Siswa pada Pembelajaran Daring - Sukamto, Sukamto; Mahmudah, Fitri Nur (Universitas Negeri Surabaya, 2022)
Online learning is one option in an effort to reduce the spread of the COVID-19 virus in schools. So that educators are required to be able to prepare media and learning methods in this online learning process. Several factors that influence the achievement of learning competencies include student activity, teacher performance in teaching, learning media, methods used and a conducive learning environment. This study tries to explore and describe the teacher's efforts in increasing student activity in online learning. The type of research used in this research is qualitative research with a case study approach. The results of the study show that there are many obstacles that arise from the online learning process carried out during the covid 19 pandemic, starting from the inactivity of students during the learning process, the availability of facilities and infrastructure both from the educators and students' side, internet networks and the availability of data quotas. All have an effect on the learning process carried out by teachers in online classes. The conclusion of this study is that teachers must try to innovate and be creative at the planning, implementation and evaluation stages of learning with this online form of learning. Teachers must follow and master the development of information technology in order to improvise in choosing the right learning models and methods for their students. The government, in collaboration with schools, must provide assistance related to facilities and infrastructure as well as the implementation of training for teachers in order to increase the capacity of teachers to face the challenges of online learning during the COVID-19 pandemic.